Islamic Center Di Pekanbaru Dengan Pendekatan Arsitektur Ekspresionisme - Dwiki Hermawan; Pedia Aldy; Mira Dharma Susilawaty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Muslims in the past were very close to the Islamic doctrine to lived their daily lives, even during the Abbasid Caliphate, Islam had won its victory. On that time, Muslims producedmany discoveries and technologies, almost in all fields of science while they still prioritized the aqeedah and morals taught by Islam. Muslims today can regain their heyday by advancedthe fields of science and technology that will match together with educational facilities and establishment for Muslims. One of these efforts is to build an Islamic Center. The design ofthe Islamic Center in Pekanbaru aims to facilitate the activities of Islamic scientific development in Pekanbaru and also to study the insights of Islamic religion and develop it as the axis of Islamic civilization. The Expressionism Architecture approach is used to be ableto demonstrate the form of buildings that can communicate the feelings and emotions which are created so that the building form has more variation and has a strong attraction for thelocal society to visit this Islamic Center. The design of the Islamic Center uses concept